Genetic and environmental effects on scores of conformation, precocity and muscling in long yearling Nellore cattle - Barrozo, Diego [UNESP]; Mattar, Maira; Tholon, Patricia; De Oliveira, João Ademir [UNESP]; Scalez, Daiane Cristina Becker [UNESP]; De Queiroz, Sandra Aidar [UNESP] (Universidade Estadual de Londrina, 2015)
The visual scores for conformation (C), precocity (P) and muscle (M) are used to indirectly assess traits related to termination and carcass composition. This study analyzes how age of dam at calving (AC), long yearling age (YA) and long yearling weight (YW) of the animal affect the scores of Nellore cattle, and estimates their heritability. Regression functions were estimated to determine the AC, YA and YW effects on C, P and M scores after the contemporary group (CG) effect being absorbed. The heritabilities were estimated by restricted maximum likelihood using four different models that included animal additive genetic effect as random and different covariates (AC, YA and YW) as fixed effects. The regression analysis showed that the covariates, either linear or quadratic, significantly influenced the scores of C, P and M. The determination coefficients of the models for YA and AC were small, probably due to the CG bias removal. The heritability estimates for the scores ranged from 0.13 to 0.36 for C; 0.32 to 0.36 for P; and, 0.35 to 0.38 for M, for all models, indicating that C, P and M respond to direct selection. The classification of animals according to their breeding values, especially in relation to C, varied according to the environmental effects included in the models.
Keywords: Calving age; Genetic evaluation; Heritability; Long yearling age; Long yearling weight